Microplastic emissions and degradation mechanisms in artificial turf systems – analytical detection, and future directions - Afsana Sharmin; Mansoor Ahmad Bhat; Nacho Martin-Fabiani-Carrato; Tanja Radu (2026)
The environmental impact of artificial turf systems is receiving increasing attention, particularly in relation to the release of microplastics. Here, our aim is to review recent studies on microplastic emissions from artificial sports fields, with an emphasis on environmental factors such as ultraviolet radiation, temperature fluctuations, rain, and mechanical wear, which all contribute to the fragmentation of synthetic fibres and infills. This study also reviews the leaching of toxic chemicals and microplastics sources in the artificial turfs. We summarise and discuss various analytical techniques, including Fourier transform infrared spectroscopy, scanning electron microscope, and pyrolysis–gas chromatography–mass spectrometry, employed to detect and quantify the release of microplastics and different contaminants from artificial turf to the environment. We identify significant gaps in current research, specifically determining degradation rates of artificial turf, and the detection and release characterisation of harmful substances like microplastics, heavy metals and polycyclic aromatic hydrocarbons from it. We highlight a need for further standardised methods, comprehensive long-term and accelerated studies to accurately assess the full ecological impact of microplastic release fromartificial turf systems.